MODEL OF MARKETING PERFORMANCE : ROLE OF INNOVATION CAPABILITY IN WOMEN ENTREPRENEURS - Octavia, Ade; Sriayudha, Yayuk (Dinasti International Journal of Management Science, 2021)
ABSTRACT The uniqueness and distinctive character of a woman, makes women prefer to run entrepreneurship. The ability of women entrepreneurs to develop product innovation provides a competitive advantage that can reflect marketing performance. Marketing performance as an important challenge in management as well as the key to the success of business actors as a result of market strategy. The purpose of study was to analyze a hypothetical model of women's entrepreneurial marketing performance. The specific objective of the study was to investigate the relationship between women's entrepreneurship and marketing performance mediated by the innovation capability of women entrepreneurs. The research design applied was a quantitative research design by forming a model and testing the model. A survey was conducted using a sample of 100 respondents of women entrepreneurs. A structured questionnaire was used to elicit information from the respondents and simple random sampling method was used to select the samples. In this study, partial least squares SEM (PLS-SEM) was used for data analysis.. The instrument that was validated and its reliability measured was analysed using descriptive and inferential statistics. The results of the study show that women's entrepreneurship have significant influence to marketing performance, both directly and indirectly, which is mediated by innovation capability. Recommendations were given to women entrepreneurs that they should be putting more emphasis on this relatively new approach of innovation capability thereby creating marketing performance. Keywords: innovation, marketing performance, SMEs, women's entrepreneurship